Something Cute by SN / Ainnur Shihan Ahmad Zahrullail and Nadia Hanis Ismail - Ahmad Zahrullail, Ainnur Shihan; Ismail, Nadia Hanis (2022)
“One can never have enough socks” is our business tagline which means socks is one of our necessities and everyone must have at least 3 and more socks in their wardrobe. We choose Something Cute By SN as our name because we only offer cute products that can make the customer unable to stop themselves from buying it. Since this is partnership business, we also combine the initials of our name which is S for Shihan and N for Nadia at the end of our business name. The main objective of our business is to supply high quality socks and footwear to our customers at an affordable price. We started our business on 14th May 2022 by using Facebook as our main platform. Customers can browse our Facebook page (https://www.facebook.com/somethingcutebysn/) to find out the available designs and then they can purchase our products via Messenger or WhatsApp. We already provided the link of our number in case our customers have any inquiries about our product. Our targeted customers are actually teenagers since we offer modern and esthetic design which is preferred by them nowadays. But we also receive orders from adults aged 30 and above. This is not surprising at all because our product can actually be worn by everyone because most of our designs are suitable for everyone regardless of their age and gender. They said that they will feel younger when they wear our products. Since the first day of our business, we received huge numbers of positive feedback from customers regarding the quality of our socks or how comfortable they feel when they wear our product. Products from Something Cute By SN were sold over 50 pcs in just 10 days. This is the proof that our business has the potential to go even further after this.